Effect of butanol extract of maturated mahkota dewa (Phaleria macrocarpa) fruit on kidney tissue of Mice (Mus musculus) - ARIF SOEKSMANTO (Society for Indonesian Biodiversity, 2006)
Mahkota dewa (Phaleria macrocarpa (Scheff.) Boerl.) is very popular recently because it is presumed as traditional medicine which can conquer various diseases, but research on the plant is still difficult to find. Although mahkota dewa is very popular as medicinal plants, it is very poisonous, especially if it is directly consumed which can cause swollen, sprue, numb at tongue, fever, even unconscious. A research was conducted to find out effect of sub chronic dosage of butanol extract of maturated mahkota dewa fruit. Observation was carried out on kidney tissue which is susceptible to chemicals entering body. Dosage of butanol extract of 0; 42.5; 85 and 170 mg/kg body weight was administered intra peritoneal to mice. The result showed that butanol extract of maturated mahkota dewa fruit with dosage until 85 mg/kg body weight did not affect kidney tissue. At dosage 170 mg/kg body weight, a light necrosis on proximal convoluted tubules was occurred.Â© 2006 Jurusan Biologi FMIPA UNS SurakartaKey words: Phaleria macrocarpa, plant extract, Mus musculus, kidney, necrosis